Advances in pediatric heart failure and treatments. Issue 1 (July 2015) - Rossano, Joseph W.; Dipchand, Anne I.; Hoffman, Timothy M.; Singh, T.P.; Jefferies, John L.
Abstract: Heart failure remains a significant contributor to morbidity and mortality in pediatric patients with congenital and acquired heart diseases. However, there are several new promising therapies for acute and chronic heart failures including the development of new pediatric specific ventricular assist devices. There remains a need for collaborative research including the creation of a large-scale registry of pediatric heart failure, increased utilization of genetic testing, and an improved understanding of the optimal model of disease management that maximizes quality care.